The Javanese Mystical Epistemology in Kitab Primbon Betaljemur Adammakna and Its Implication to Inclusivism - Mahmudi Mahmudi; Ahsanul Anam (Teosofia: Indonesian Journal of Islamic Mysticism, 2024)
Javanese culture is rich. It has been practiced from generation to generation and still exists today. One kind of Javanese treasury in the form of work is Kitab Primbon (Book of forecasts), which is often used as a reference in various aspects of the life of Javanese people, such as marriage, business, work, predicting the future, and even knowing someone's character. This study aims to investigate the Kitab Primbon Betaljemur Adammakna, a book owned by Sultan Hamengku Buwono of Yogyakarta, which was rewritten by Pangeran Harya Tjakraningrat, regarding its epistemology and implications for inclusive attitudes. This study is classified as qualitative research, with the primary data collected from Kitab Primbon Betaljemur Adammakna. This study applies descriptive analysis. The results reveal that this book has Javanese mystical epistemology. Even though it is considered not to have a rational basis, it is believed to be valid among Javanese people and is thus still used as a reference for their lives. The book has profound implications for attitudes of tolerance in pluralistic Indonesian society. Through recognition of the plurality of spiritual paths, awareness of unity in diversity, karma, and compassion, and an attitude of humility and piety, this book encourages individuals and society to develop an inclusive attitude of tolerance and respect for the diversity of religions and beliefs.Contribution: This study provides an understanding of tolerance attitudes inspired by the local wisdom of Javanese people, i.e., Kitab Primbon.